IPSATIVE METHODOLOGY IN THE STUDY OF MARRIAGE AND FAMILY PRACTICES OF PARTNERSHIP AND PARENTHOOD - Yatsyna, Olena (PSYCHOLOGICAL JOURNAL, 2017)
Experimental researches on the semantics of consciousness show individual systems of meanings in individual consciousness, through the light of which a subject perceives the world, himself /herself and others. In postmodern times, scholars draw their attention to the description of social and psychological practices presented in this reality as ways of life-construction, connected with its interpretation of sociality and the search for personal identities, as it is legitimized by postmodernism. Changes in marriage and family practices of partnership and parenthood naturally transform the perception of a family, marriage, partnership and parenthood, and therefore require another scientific explanation that has not yet been reflected in the psychology of the family. The choice of the research methodology was made in favour of the ipsative approach, which, according to scholars, minimizes the «effect of social desirability» as a normative prescription. The task is to analyse the questionnaire’s results, which reflect the structure reconstruction of role identities representations in partnership and parenthood everyday practices. According to the results we have distinguished 8 groups of object-descriptors. They determine the final structure of the clusters, which corresponds to the chosen optimality criterion. The cluster analysis confirmed the assumption that postmodern transformations of marriage and family practices of partnership and parenthood are conditional on social and psychological phenomena, connected with changes of meanings in the structural and functional setup of practices as well as with multiplicity of identity as an identification model of role behaviour in conditions of another sociality. The study has shown that formed partnership and parenthood practices have different functionality for spouse / partners and they are distinguished both by meanings, value orientations on their creation, and the multiplicity of identities presented. In order to reconstruct the structure of respondent’s representations about role identifications in everyday situations, we consider promising the idea of studying the psycho-semantic space of role positions connected with partnership and parenthood practices.